The Creation of a Collaborative Business Strategy in the b2b Network Project - Case Study - Kot , Mateusz (Studia Oeconomica Posnaniensia, 2018)
Projects co-created by different companies are quite challenging. Much of the challenge involves answering the question- how to develop a business strategy to increase the value from co-operation? On the one hand co-operation can be very fruitful for each and every side of the project network, but on the other hand close co-operation involves becoming less self-sufficient. This paper contains a case study of a b2b project co-created by four companies operating in the garden industry. Concepts of strategic coherence, adaptation and organization openness were used to analyze the case study in order to recognize the influence of different elements of the relationship on the effects of co-operation. The results show the significance of acquiring the right partners for a project and making sure that comparably high input is presented by actors in order to create value for the end-costumer. In conclusion, the main critical success factor for b2b projects are identified.